2013
DOI: 10.3109/07357907.2013.793699
|View full text |Cite
|
Sign up to set email alerts
|

Association of CTLA-4 Polymorphisms with Improved Overall Survival in Melanoma Patients Treated with CTLA-4 Blockade: A Pilot Study

Abstract: CTLA-4 blockade with monoclonal antibodies can lead to cancer regression in patients with metastatic melanoma (MM). CTLA-4 gene polymorphisms may influence the response to anti-CTLA-4 antibodies although few data are available regarding this issue. We analyzed six CTLA-4 single nucleotide polymorphisms (-1661A > G, -1577G > A, -658C > T, -319C > T, +49A > G, and CT60G > A) in 14 Italian MM patients and 45 healthy subjects. We found a significant association between the -1577G/A and CT60G/A genotypes and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Moreover, there were 30 studies with 9675 cases and 9623 controls for rs3087243 [12-15, 17, 23-25, 27-29, 31, 32, 35, 37, 40, 41, 44, 45, 47, 53, 54, 61, 63, 65, 66, 73-75]. Additionally, rs4553808 was in 17 studies [12, 14, 15, 23, 28, 29, 31, 37, 41, 44, 47, 49, 51, 52, 62, 73, 76], rs5742909 was in 32 studies [12, 14, 15, 20, 24, 25, 28-30, 32, 34, 35, 39-41, 45, 47, 52-54, 56, 57, 59, 62, 63, 65, 66, 70, 73, 76, 77], rs733618 was in 14 studies [13, 23, 28, 37, 44, 47, 51, 52, 62, 73-76, 78], and they were analysed. Of the 67 studies, 9 presented a significant deviation from HWE (5 studies on rs231775 [11, 13, 34, 51, 66], 4 studies on rs4553808 [51, 62…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there were 30 studies with 9675 cases and 9623 controls for rs3087243 [12-15, 17, 23-25, 27-29, 31, 32, 35, 37, 40, 41, 44, 45, 47, 53, 54, 61, 63, 65, 66, 73-75]. Additionally, rs4553808 was in 17 studies [12, 14, 15, 23, 28, 29, 31, 37, 41, 44, 47, 49, 51, 52, 62, 73, 76], rs5742909 was in 32 studies [12, 14, 15, 20, 24, 25, 28-30, 32, 34, 35, 39-41, 45, 47, 52-54, 56, 57, 59, 62, 63, 65, 66, 70, 73, 76, 77], rs733618 was in 14 studies [13, 23, 28, 37, 44, 47, 51, 52, 62, 73-76, 78], and they were analysed. Of the 67 studies, 9 presented a significant deviation from HWE (5 studies on rs231775 [11, 13, 34, 51, 66], 4 studies on rs4553808 [51, 62…”
Section: Resultsmentioning
confidence: 99%
“…Genetic analysis of 64 ipilimumab-treated melanoma patients uncovered a correlation between mutational load and clinical benefit and identified a neo-antigen landscape specific to tumors that are highly responsive to treatment 220 . Some specific genetic mutations 221 and the presence of particular single-nucleotide polymorphisms 222 have also been shown to predict clinical response. Interestingly, the single-nucleotide polymorphisms (SNPs) that correlated with beneficial clinical response did not show any correlation with the occurrence or severity of adverse events 222 , suggesting that the mechanisms underlying efficacy and toxicity do not overlap entirely and can thus be differentially targeted when designing future immunomodulatory mAbs for greater therapeutic index.…”
Section: Expert Opinion: Is It Possible To Selectively Increase Samentioning
confidence: 99%
“…Some specific genetic mutations 221 and the presence of particular single-nucleotide polymorphisms 222 have also been shown to predict clinical response. Interestingly, the single-nucleotide polymorphisms (SNPs) that correlated with beneficial clinical response did not show any correlation with the occurrence or severity of adverse events 222 , suggesting that the mechanisms underlying efficacy and toxicity do not overlap entirely and can thus be differentially targeted when designing future immunomodulatory mAbs for greater therapeutic index. This study also supports an earlier hypothesis that some mutations considered silent passengers should instead be classified as immune determinants 223 that collectively define immunogenicity and susceptibility to antitumor effector mechanisms employed by the immune system.…”
Section: Expert Opinion: Is It Possible To Selectively Increase Samentioning
confidence: 99%
“…After analyzing 6 CTLA-4 single nucleotide polymorphisms (SNPs) (−1661A>G, −1577G>A, −658C>T, −319C>T, +49A>G, and CT60G>A) in malignant melanoma patients, a recent study found that the −1577G/A and CT60G/A genotypes had better overall survival and response to ipilimumab treatment (104). Different SNPs alter CTLA-4 expression, so response to ipilimumab can differ depending on the genotype.…”
Section: Future Directionsmentioning
confidence: 99%